Measurement of Motor Evoked Potential in Acute Ischemic Stroke: Based on Latency, Amplitude, Central Motoric Conduction Time and Resting Motor Threshold - Tugas Ratmono; Andi Wijaya; Cahyono Kaelan; Andi Asadul Islam; Ferry Sandra (The Indonesian Biomedical Journal, 2016)
BACKGROUND: After stroke, there are dynamic changes of motor evoked potential (MEP), including latency, amplitude, central motoric conduction time (CMCT) and resting motor threshold (RMT) in cerebral. However, latency, CMCT, amplitude and RMT have not been clearly shown in acute ischemic stroke patients with motoric function impairment based on Modified Motoric Research Council Scale (MRCs).METHODS: Patients with motoric function impairment after acute ischemic stroke were recruited, scored based on MRCs and grouped. Latency, amplitude, CMCT and RMT (% intensity) was measured using transcranial magnetic stimulation (TMS). Latency, amplitude, CMCT and RMT of subjects based on affected hemisphere (AH) and unaffected hemisphere (UH); stroke onset; and motoric severity; were analyzed and compared statistically.RESULTS: Thirty-seven subjects with complete assessments were selected. Results of MEP size measurement between AH and UH showed that latency, amplitude, CMCT and RMT of AH and UH were significantly different (p<0.05). In accordance to AH and UH results, latency, amplitude, CMCT and RMT of mild, moderate and severe groups based on motoric severity, showed that latency and CMCT were prolonged, RMT was increased, while amplitude was decreased along with severity increment. The amplitude and RMT among the groups were significantly different with p=0.034 and p=0.029, respectively.CONCLUSION: MEP size measurement including latency, amplitude, CMCT and RMT have significant different in AH and UH. In addition, amplitude and RMT were significantly different in MRCs groups, therefore the MEP size measurement could be suggested as prognostic tool.KEYWORDS: MEP, latency, amplitude, CMCT, RMT